New ways of working: Differences between autonomy support and flexible work arrangements and relations to employee stress - Dewi, Inten Dwi Puspa; Salendu, Alice (Universitas Mercu Buana Yogyakarta, 2023)
The aftermath of COVID-19 has led to the widespread adoption of flexible work arrangements that promote employee’s job satisfaction and engagement across industries and organizations worldwide. Although the implementation of flexible work arrangements is generally regarded favorable, research suggests that it can also increase adverse effects on employee job characteristics, such as increased workload and blurred lines between work and personal life. Inconsistencies in the efficacy of diverse work arrangements within industries and organizations have not improved employees' well-being, such as engagement, satisfaction, and commitment at work. Using an experimental method, this study investigates how leaders’ approaches to autonomy influence employees’ stress levels in various categories of work arrangement manipulation scenarios. This study involved 156 participants who met the sample criteria: active employees in Indonesia with a minimum of 2 years of work experience, aged 22 to 64, and familiar with both conventional and flexible work arrangements. Significant differences in work stress were found in the four work scenarios, with the highest mean in the group with a leader who controlled autonomy in traditional work arrangements (M=39.73) and the lowest mean in the group with a leader who supported autonomy in flexible work arrangements (M=30.56). These findings indicate that a leader's orientation toward supporting employee autonomy in flexible work arrangements could potentially protect employees from potential work stress in the post-pandemic period.